2015
DOI: 10.1002/eji.201445403
|View full text |Cite
|
Sign up to set email alerts
|

IL‐Y, a synthetic member of the IL‐12 cytokine family, suppresses the development of type 1 diabetes in NOD mice

Abstract: The IL-12 family of heterodimeric cytokines, consisting of IL-12, IL-23, IL-27, and IL-35, has important roles in regulating the immune response. IL-12 family members are comprised of a heterodimer consisting of α and β chains: IL-12 (p40 and p35), IL-23 (p40 and p19), IL-27 (Ebi3 and p28), and IL-35 (Ebi3 and p35). Given the combinatorial nature of the IL-12 family, we generated adenoviral vectors expressing two putative IL-12 family members not yet found naturally, termed IL-X (Ebi3 and p19) and IL-Y (p40 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 52 publications
0
26
1
Order By: Relevance
“…However, IL-30 was demonstrated to function as an agonistic cytokine via the gp130 signaling pathway similar to IL-6, either by itself or associated with other molecules, such as IL-12p40 (15, 16), cytokine-like factor 1 (CLF) (61), IL-6Rα (62), forming p28/IL-6Rα classic signaling, p28/sIL-6Rα trans -signaling, and p28 signaling (Figure 4). …”
Section: Il-y (P28/p40)mentioning
confidence: 99%
See 3 more Smart Citations
“…However, IL-30 was demonstrated to function as an agonistic cytokine via the gp130 signaling pathway similar to IL-6, either by itself or associated with other molecules, such as IL-12p40 (15, 16), cytokine-like factor 1 (CLF) (61), IL-6Rα (62), forming p28/IL-6Rα classic signaling, p28/sIL-6Rα trans -signaling, and p28 signaling (Figure 4). …”
Section: Il-y (P28/p40)mentioning
confidence: 99%
“…These suppressive effects seemed to be ascribed to antagonizing the activation of STAT1 and STAT3 pathways induced by IL-27 and IL-6, both of which signal through the gp130 receptor (15). Moreover, recent studies using adenovirus vector expressing p28/p40 (IL-Y) suggested that treatment of prediabetic non-obese diabetic mice prevented the onset of hyperglycemia with reduced expression of inflammatory mediators such as IFN-γ (16). Interestingly, in this study, p28/p40 was demonstrated to be able to significantly stimulate a unique cytokine and chemokine expression profile as well as to activate STAT3, in part, through a pathway involving WSX-1 (16).…”
Section: Il-y (P28/p40)mentioning
confidence: 99%
See 2 more Smart Citations
“…The IL-12 family cytokines are α/β heterodimers consisting of one α subunit (IL-23p19, IL-27p28, IL-12p35) and one β chain (IL-12p40, Ebi3) [14,15]. Although there are currently four known members in the family, the predictable range of combinations is six and it is conceivable that additional pairings such as IL-23p19/Ebi3 are possible [12,[14][15][16][17]. In this study, we sought to discover additional IL-12 members that might exist in nature.…”
mentioning
confidence: 99%